Human Immunodeficiency Virus Infection Newly Diagnosed at Autopsy in New York City, 2008–2012. (30th September 2015) - Ramaswamy, Chitra; Ellman, Tanya M.; Myers, Julie; Madsen, Ann; Sepkowitz, Kent; Shepard, Colin
Abstract : Decedents with new HIV diagnosis at autopsy were predominantly male, aged 13-64 years, non-white, unmarried, less than college educated, and residents of an impoverished neighborhood. The strongest independent correlate of new HIV diagnosis at autopsy was age ≥65 years. Abstract: Background.  Studying the most extreme example of late diagnosis, new HIV diagnoses after death, may be instructive to HIV testing efforts. Using the results of routine HIV testing of autopsies performed by the Office of Chief Medical Examiner (OCME), we identified new HIV diagnoses after death in New York City (NYC) from 2008 to 2012. Methods.  Population-based registries for HIV and deaths were linked to identify decedents not known to be HIV-infected before death. Multivariable logistic regression models were constructed to determine correlates of a new HIV diagnosis after death among all persons newly diagnosed with HIV and among all HIV-infected decedents receiving an OCME autopsy. Results.  Of 264 893 deaths, 24 426 (9.2%) were autopsied by the NYC OCME. Of these, 1623 (6.6%) were infected with HIV, including 142 (8.8%) with a new HIV diagnosis at autopsy. This represents 0.8% (142 of 18 542) of all new HIV diagnoses during the 5-year period. Decedents newly diagnosed with HIV at OCME autopsy were predominantly male (73.9%), aged 13–64 years (85.9%), non-white (85.2%), unmarried (81.7%), less than college educated (83.8%), and residents of an impoverished neighborhood (62.0%). Of all HIV-infected OCME decedents aged ≥65 years (n = 71), 22.0% were diagnosed at autopsy. The strongest independent correlate of new HIV diagnosis at autopsy in both multivariable models was age ≥65 years. Conclusions.  Human immunodeficiency virus diagnoses first made after death are rare, but, when observed, these diagnoses are more commonly found among persons ≥65 years, suggesting that despite highly visible efforts to promote HIV testing community-wide, timely diagnosis among older adults living in impoverished, high-prevalence neighborhoods may require additional strategies.